2013
DOI: 10.1371/journal.pone.0081632
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Syzygium aromaticum-Derived Triterpenes on Postprandial Blood Glucose in Streptozotocin-Induced Diabetic Rats Following Carbohydrate Challenge

Abstract: PurposeRecent reports suggest that the hypoglycaemic effects of the triterpenes involve inhibition of glucose transport in the small intestine. Therefore, the effects of Syzygium spp-derived triterpenes oleanolic acid (OA) and maslinic acid (MA) were evaluated on carbohydrate hydrolyzing enzymes in STZ-induced diabetic rats and consequences on postprandial hyperglycaemia after carbohydrate loading. MethodsWe determined using Western blot analysis the expressions of α-amylase and α-glucosidase and glucose trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
48
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 32 publications
(37 reference statements)
2
48
0
1
Order By: Relevance
“…These results were in agreement with previous observations from studies conducted in our laboratory (Mapanga et However, both OA and MA had no significant effect on plasma insulin concentrations in the STZ-diabetic rats suggesting that the blood glucose lowering effects may be exerted via extra-pancreatic mechanisms. We have previously reported that OA and MA could prevent postprandial hyperglycaemia through the down-regulation of key intestinal carbohydrate hydrolyzing enzymes such as α-amylase and α-glucosidase as well as intestinal glucose transporters such as SGLT1 and GLUT2 (Khathi et al, 2013). The results of this study showed that the plasma ghrelin levels were significantly higher in the STZ-diabetic animals possibly as a result of the decreased plasma insulin levels (Buss et al, 2014).…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…These results were in agreement with previous observations from studies conducted in our laboratory (Mapanga et However, both OA and MA had no significant effect on plasma insulin concentrations in the STZ-diabetic rats suggesting that the blood glucose lowering effects may be exerted via extra-pancreatic mechanisms. We have previously reported that OA and MA could prevent postprandial hyperglycaemia through the down-regulation of key intestinal carbohydrate hydrolyzing enzymes such as α-amylase and α-glucosidase as well as intestinal glucose transporters such as SGLT1 and GLUT2 (Khathi et al, 2013). The results of this study showed that the plasma ghrelin levels were significantly higher in the STZ-diabetic animals possibly as a result of the decreased plasma insulin levels (Buss et al, 2014).…”
Section: Discussionmentioning
confidence: 51%
“…Various medicinal plant extracts have been reported to significantly reduce food intake possibly through the reduction of plasma ghrelin levels (Bast et al, 2002;Fong, 2002). Studies conducted in our laboratory have shown that Syzygium aromaticum-derived oleanolic acid (OA) and maslinic acid (MA) reduce blood glucose concentrations in STZ-induced diabetic rats in sub-chronic studies through a variety of mechanisms (Khathi et al, 2013;Mkhwanazi et al, 2014;Musabayane et al, 2010;Ngubane et al, 2011). Furthermore, these triterpenes have previously been reported to reduce food intake through unknown mechanisms (Khathi et al, 2013;Mkhwanazi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to studies on the inhibition of amylase and glucosidase activities, in recent years new data have been reported showing that OA can also repress the expression of these proteins in the small intestine (Gabás-Rivera et al, 2013;Khathi et al, 2013), in addition to the glucose transporters SGLT1 and GLUT2, involved in the absorption of the saccharide from the lumen of the small intestine to the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…Before induction, all rats were fasted 12 h (Ngueguim et al, 2016). Rats with serum glucose level above 300 mg/dl were Fokunang et al 125 considered as diabetic (Khathi et al, 2013).…”
Section: Induction Of Diabetesmentioning
confidence: 99%